2020
DOI: 10.1186/s13567-020-00856-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the microRNA expression profiles of chicken dendritic cells in response to H9N2 avian influenza virus infection

Abstract: MicroRNA (miRNA) plays a key role in virus-host interactions. Here, we employed deep sequencing technology to determine cellular miRNA expression profiles in chicken dendritic cells infected with H9N2 avian influenza virus (AIV). A total of 66 known and 36 novel miRNAs were differently expressed upon H9N2 infection, including 72 up-regulated and 30 down-regulated miRNAs. Functional analysis showed that the predicted targets of these miRNAs were significantly enriched in several pathways including endocytosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…It can also detect miRNAs with very low copy numbers, which reflect either a low expression level in the tissue or a contribution from minor cell types such as blood or adipose or connective tissues in the biopsy specimen [ 39 41 ]. In this experiment, the number of up-regulated miRNAs was more than down-regulated miRNAs, which was consisted with the other researches of miRNA sequencing in chicken [ 42 , 43 ]. The pathways for up-regulated miRNA target genes were cell apoptosis, nucleic acid metabolism, regulation of protein metabolism, glycolysis/gluconeogenesis, PPAR signaling pathway and other metabolic-related processes, the down-regulated miRNA target genes were mainly enriched in Toll -like receptor signaling pathway, which was the immune-related process.…”
Section: Discussionmentioning
confidence: 99%
“…It can also detect miRNAs with very low copy numbers, which reflect either a low expression level in the tissue or a contribution from minor cell types such as blood or adipose or connective tissues in the biopsy specimen [ 39 41 ]. In this experiment, the number of up-regulated miRNAs was more than down-regulated miRNAs, which was consisted with the other researches of miRNA sequencing in chicken [ 42 , 43 ]. The pathways for up-regulated miRNA target genes were cell apoptosis, nucleic acid metabolism, regulation of protein metabolism, glycolysis/gluconeogenesis, PPAR signaling pathway and other metabolic-related processes, the down-regulated miRNA target genes were mainly enriched in Toll -like receptor signaling pathway, which was the immune-related process.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that innate immunity and adaptive immunity are both important in the prevention of chicken coccidiosis 10 . However, in the early stages of infection, the innate immunity of the host ensures an immediate response to invading parasites, and activation of innate immune responses primarily depends on innate immune receptors 11 . Toll‐like receptors (TLRs) are major components of innate immune system in vertebrate species, and these transmembrane proteins are responsible for microbial recognition.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, in the early stages of infection, the innate immunity of the host ensures an immediate response to invading parasites, and activation of innate immune responses primarily depends on innate immune receptors. 11 Toll-like receptors (TLRs) are major components of innate immune system in vertebrate species, and these transmembrane proteins are responsible for microbial recognition. Once activated by specific ligands such as bacterial lipopolysaccharide (LPS), glycolipids, viral nucleic acids and CpG Oligodeoxynucleotides (CpG ODN), TLR signals can lead to the recruitment of various immune cells and generate a wide range of biologically active molecules including chemokines, cytokines and antimicrobial peptides, which stimulates the innate immune responses necessary for parasite clearance and resistance to re-infection.…”
mentioning
confidence: 99%
“…One early study reported DCs can be grown by co-culturing chicken bone marrow (BM)derived cells with chicken granulocyte-macrophage stimulating factor (GM-CSF) and chicken interleukin 4 (IL-4) [30]. In this study, we culture bone-derived chicken dendritic cells (ck-BM-DC) to examine gene expression levels of IFN-α, TLR-3, TLR-7, MHC-I, IL-1β, IL-6, Mx, Casp-3, and Casp-8 of DCs infected with AIV There are limited studies examining the interactions between chicken DCs and AIV [25,[31][32][33]. The exact nature of how AIV infections affect DCs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%